Sex-specific regional grey matter volume correlates of daily activities - Tsukasa Ueno (Nature Portfolio, 2018)
Abstract The human brain is plastic and continuously modified throughout life by our daily experiences and behaviours. However, no reports have comprehensively investigated structural brain correlates of our daily activities, including possible sex differences. In this study, we examined the relationship between a self-reported 24-hour Life-Log and regional brain volume measured by structural magnetic resonance imaging. We analysed brain volumes of 64 males and 53 females that were obtained from multiple scanning sites. We found several sex-specific correlations, including a positive correlation between superior frontal gyrus (Brodmann area 8) volume and domestic work hours, and a negative correlation between volume in the same region and job-work hours. Despite being a cross-sectional study, this study provides empirical evidence for how and to what extent brain structure is correlated with everyday activity.